“Quilombo urbano”, Liberdade, Camboa e Fé em Deus: identidade, festas, mobilização política e visibilidade na cidade de São Luís, Maranhão - Assunção, Ana Valéria Lucena Lima. (2017)
The neighborhoods, Liberdade, Camboa and Fé em Deus, referenced in this research, are located in the municipal of São Luís, Maranhão. Residents described here have similar origins, many coming from Alcantara, and have life stories marked by cooperation and practices of reciprocity in addition to many of them being relatives. This dissertation has the objective of understanding social experiments, construction social events, the construction of cultural events, religious festivals and rituals of the neighborhoods Liberdade, Camboa and Fé em Deus, through residents’ narratives. As such, I search how a sense of belonging is activated by social agents through use of the term “Quilombo urbano” or in English, “urban maroon republic”. Data from this research was collected through interviews, observations and secondary resources. This research enabled perception of strong resident participation in religious celebrations, cultural manifestations and organizations that struggle for positive visibility. In addition, shared experiments by these residents can represent an element of collective identity affirmation.